Analisis Kebugaran Jasmani dalam Meningkatkan Performa Olahraga Siswa SMA: Studi Literature Review - Muhammad Sultan Al-Rahmatsyah; Ilham; Tri Bayu Norito; Wawan Junresti Daya; Boy Indrayana (S&Co Publishing, 2026)
Physical fitness is an important factor in supporting the health, physical activity, and sports performance of high school students. Low levels of physical activity due to technological developments and sedentary lifestyles lead to a decline in students' physical fitness, which impacts their ability to participate in learning and sports activities. This study aims to analyze the role of physical fitness in improving high school students' sports performance through a literature review study. The research method used a literature review by collecting various journal articles, books, and relevant previous research through Google Scholar and other scientific journals. Data were analyzed descriptively by comparing and summarizing the results of previous studies. The results of the study indicate that physical fitness has a positive relationship with sports performance, physical ability, health, and student participation in physical education (PJOK) learning. Students with a good level of fitness tend to be more active, less tired, and able to demonstrate more optimal sports performance. Therefore, a structured and sustainable physical activity program is needed in the school environment to improve students' physical fitness and support academic and sports achievements.